IMPLEMENTASI METODE TECHNOMETRIC SEBAGAI UPAYA MENINGKATKAN MUTU PENDIDIKAN DI SMK KELOMPOK PARIWISATA - Mohammad Adam Yerusalem (Universitas Negeri Yogyakarta, 2007)
Abstract The aim of this research is getting information about: 1) to know the component contribution of technology on the Sekolah Menengah Kejuruan (SMK) according to Technometric Method; 2) to know application degree of the technology component on each school; 3) to know technology developing priority on that school. The kind of this research is survey. This research objects are Public SMK that chosen by purposive technique. The data resources in this research are: facilities (technoware), abilities (humanware), facts (infoware), and frameworks (orgaware) that adopted from SMK’s Minimum Services Standard. Analysis method is techno metric. By thid research, we have information about: 1) the highest of component contribution in Public SMK is orgaware, then inforware, humanware, and technoware is lowest. In the otherhand, in private SMK is humanware, then inforware, orgaware, and technoware in the lowest. 2) according to assessment scale for technologycontribution coefficient (TCC) has known that the grade of quality of Public SMk and Private SMK on good qualification. 3) Through problem mapping with technometric analysis, priorities of school quality improvement can be decided. Priority of quality improvement in Public SMK begin from human abilities, then facilities, organization, and fact/ information. While in Private SMK starts from facilities, then human abilities, fact/ information, and organization for the last. Keywords: technology, components contribution, technology-contribution coefficient